Предмет: Математика,
автор: Аноним
Как решить (2x+y=11
(-3x+y=-9
Ответы
Автор ответа:
1
2х + y = 11, y = 11-2x
-3x +y = -9; -3x + 11 - 2x = -9
-3x + 11 - 2x = -9
-5x +11 = -9
-5x = -9 - 11
- 5x = - 20
x = -20: (-5)
x = 4
Ответ: х = 4
-3x +y = -9; -3x + 11 - 2x = -9
-3x + 11 - 2x = -9
-5x +11 = -9
-5x = -9 - 11
- 5x = - 20
x = -20: (-5)
x = 4
Ответ: х = 4
Автор ответа:
2
решение метод алгебраич. сложения
2х+у=11
-3х+у= -9 система
2х+у=11
3х-у=9 система
5х=20
х=4
подставляем
2*4+у=11
8+у=11
у=3
Похожие вопросы
Предмет: Алгебра,
автор: aigulars123
Предмет: Биология,
автор: Artur0760
Предмет: Математика,
автор: asanali32142
Предмет: Математика,
автор: лераоооооооооооооооо
Предмет: Информатика,
автор: 0903aa